Improving Numeracy Skills for Teachers in South Buru Regency - Anderson Leonardo Palinussa; Carolina Selfisina Ayal; Eka Triana (Pascasarjana Universitas Mataram, 2026)
This community service activity aims to improve the numeracy skills of teachers in South Buru Regency through Community-Based Research (CBR) training. This approach places teachers as partners who are actively involved in the entire activity process, from the planning stage, implementation, to program evaluation. The activity was attended by 80 teachers from elementary and junior high school levels. The training materials include understanding basic numeracy concepts, the difference between numeracy and calculation skills, strategies for integrating numeracy into learning, as well as the application of numeracy in various everyday life situations. The effectiveness of the activities was measured using pre-test and post-test instruments that covered six aspects of teachers' numeracy skills assessment. The training results showed a significant improvement in all measured aspects. The average pre-test scores ranged from 50–58, while the post-test results increased to 78–85. In addition to the improvement in evaluation results, observation results also showed an increase in participation, enthusiasm, confidence, and teachers' ability to discuss and simulate numeracy learning. Thus, this activity is effective in enhancing teachers' conceptual understanding and strengthening their ability to apply numeracy learning that is more contextual, innovative, and in accordance with the needs of students in the school environment.